The (+)-Brevipolide H Displays Anticancer Activity against Human Castration-Resistant Prostate Cancer: The Role of Oxidative Stress and Akt/mTOR/p70S6K-Dependent Pathways in G1 Checkpoint Arrest and Apoptosis - Sheng, Yi-Hua (Molecules, 2020)
Because conventional chemotherapy is not sufficiently effective against prostate cancer, various examinations have been performed to identify anticancer activity of naturally occurring components and their mechanisms of action. The (+)-brevipolide H, an α-pyrone-based natural compound, induced potent and long-term anticancer effects in human castration-resistant prostate cancer (CRPC) PC-3 cells. Flow cytofluorometric analysis with propidium iodide staining showed (+)-brevipolide H-induced G1 arrest of cell cycle and subsequent apoptosis through induction of caspase cascades. Since Akt/mTOR pathway has been well substantiated in participating in cell cycle progression in G1 phase, its signaling and downstream regulators were examined. Consequently, (+)-brevipolide H inhibited the signaling pathway of Akt/mTOR/p70S6K. The c-Myc inhibition and downregulation of G1 phase cyclins were also attributed to (+)-brevipolide H action. Overexpression of myristoylated Akt significantly rescued mTOR/p70S6K and downstream signaling under (+)-brevipolide H treatment. ROS and Ca(2+), two key mediators in regulating intracellular signaling, were determined, showing that (+)-brevipolide H interactively induced ROS production and an increase of intracellular Ca(2+) levels. The (+)-Brevipolide H also induced the downregulation of anti-apoptotic Bcl-2 family proteins (Bcl-2 and Bcl-xL) and loss of mitochondrial membrane potential, indicating the contribution of mitochondrial dysfunction to apoptosis. In conclusion, the data suggest that (+)-brevipolide H displays anticancer activity through crosstalk between ROS production and intracellular Ca(2+) mobilization. In addition, suppression of Akt/mTOR/p70S6K pathway associated with downregulation of G1 phase cyclins contributes to (+)-brevipolide H-mediated anticancer activity, which ultimately causes mitochondrial dysfunction and cell apoptosis. The data also support the biological significance and, possibly, clinically important development of natural product-based anticancer approaches.